2021
DOI: 10.1108/bfj-07-2021-0837
|View full text |Cite
|
Sign up to set email alerts
|

Understanding barriers to consumers to stop washing raw poultry through in-depth interviews

Abstract: PurposeFoodborne illness from poultry may be associated with improper handling that results in cross contamination. Washing of raw poultry is one practice that can lead to cross contamination. Some consumers continue to wash raw poultry after learning that not washing raw poultry is the safe behavior. There is a need to better understand why some consumers continue this practice and identify barriers to them adopting the correct behavior.Design/methodology/approachThis research utilized qualitative, in-depth i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…(2022) observed that “habitual practices and routine behaviour,” such as how individuals washed their hands, utensils, and food were the primary risk factors contributing to food safety problems. A similar effect was observed in interviews conducted by Gilman et al. (2022), where consumers resisted adopting the correct method of washing raw poultry due to the habitual nature of the behavior.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…(2022) observed that “habitual practices and routine behaviour,” such as how individuals washed their hands, utensils, and food were the primary risk factors contributing to food safety problems. A similar effect was observed in interviews conducted by Gilman et al. (2022), where consumers resisted adopting the correct method of washing raw poultry due to the habitual nature of the behavior.…”
Section: Resultssupporting
confidence: 63%
“…For example, in their ethnographic study of Italian households, Menini et al (2022) observed that "habitual practices and routine behaviour," such as how individuals washed their hands, utensils, and food were the primary risk factors contributing to food safety problems. A similar effect was observed in interviews conducted by Gilman et al (2022), where consumers resisted adopting the correct method of washing raw poultry due to the habitual nature of the behavior. This pattern of repeated habitual behavior is consistent with the following description by Aarts and Dijksterhuis (2000, p. 53) of habit formation: "when a behavior has been performed many times in the past, future behavior becomes increasingly under the control of an automatized process."…”
Section: Habitsupporting
confidence: 63%
“…On average, each semi-structured interview lasted between forty-five minutes and one hour and each interview was recorded. During the interviews, the participants were asked common open-ended questions, customised across four semi-structured instruments to reflect participants’ roles and organisations, and formulated in light of the literature regarding Industry 4.0, innovation in the wine industry (Baron and Dimitri, 2019; Gilman et al. , 2021; Rosenlund et al.…”
Section: Methodsmentioning
confidence: 99%
“…On average, each semi-structured interview lasted between forty-five minutes and one hour and each interview was recorded. During the interviews, the participants were asked common open-ended questions, customised across four semistructured instruments to reflect participants' roles and organisations, and formulated in light of the literature regarding Industry 4.0, innovation in the wine industry (Baron and Dimitri, 2019;Gilman et al, 2021;Rosenlund et al, 2020). The common questions asked in the interviews covered the participant's knowledge and understanding of IoT, blockchain, artificial intelligence, and machine learning, whether policies and regulations acted as barriers or facilitators of adoption, and data access and management.…”
Section: Methodsmentioning
confidence: 99%
“…In a study conducted in Portugal, cleanliness, hygiene, and food safety were the main reasons why people washed their chicken meat (Cardoso, Ferreira, Truninger, Maia & Teixeira, 2021). A study in the USA revealed that the ambition to control the food preparation process, the lack of confidence in poultry processing, and the habitual nature of this behavior in daily life were the most common factors contributing to the washing of chicken (Gilman, Henley & Quinlan, 2021). Vatral, Gilman and Quinlan (2021) reported that in the United States a large part of consumers do not know what the right behavior is.…”
Section: Scientific Explanationsmentioning
confidence: 99%